EKSISTENSI TAFSIR AL-MANAR SEBAGAI TAFSIR MODERN - Subhan Subhan (fakultas Ushuluddin dan Dakwah IAIN Bone, 2018)
Interpretation is one of the arts that can teach people how to know the meaning of the Qur'an. Because in the Qur'an itself there are still verses that are not very clear (mutasyabihat). And with these interpretations, people can comment, comment, and comment on things that are not mentioned or that are not yet general and are not given in detail by the Qur'an. So with the advent of various books of interpretation, whether the study of tafisr is traditional or modern. One that has contributed greatly to the development of interpretations and interpretations of science is as found in al-Manar's interpretive text which is a part of modern interpretations. And the emphasis in that interpretation is on the use of al-ijtima’i manners.KeywordsTafsir; Tafsir al-Manar; Modern Tafsir